2022
DOI: 10.48550/arxiv.2207.10111
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ALP Dark Matter Mini-Clusters from Kinetic Fragmentation

Abstract: We show that very compact axion mini-clusters can form in models where axion-like-particle (ALP) dark matter is produced via the kinetic misalignment mechanism, which is well-motivated in pre-inflationary U (1) symmetry breaking scenarios. This is due to ALP fragmentation. We predict denser halos than what has been obtained so far in the literature from standard misalignment in post-inflationary U (1) breaking scenarios or from large misalignment. The main reason is that adiabatic fluctuations are significant … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…One main model-independent consequence is a distinct prediction for dense compact miniclusters that is presented in detail in a companion paper [26]. There is also a stochastic gravitational wave background generated by axion fragmentation as we discuss in our section 6.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…One main model-independent consequence is a distinct prediction for dense compact miniclusters that is presented in detail in a companion paper [26]. There is also a stochastic gravitational wave background generated by axion fragmentation as we discuss in our section 6.…”
Section: Discussionmentioning
confidence: 82%
“…The distinctive feature in this scenario is the momentum distribution of the axion particles. Ultimately, our analysis sets the basis to derive the phenomenological implications of this modified power spectrum, which will be presented in [26]. We will provide predictions in the explicit UV completions in another companion publication [27], deriving the precise model parameter space regions for ALP dark matter through kinetic fragmentation.…”
Section: Jcap10(2022)053mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that fragmentation might play an important role in the dynamics, as it introduces an additional scale which could alter the description above [125]. For a model of the axion-like particle, fragmentation occurs in a sizable part of the parameter space, leading to heavier miniclusters than in the standard scenario [126]. Fragmentation is expected to occur also for the QCD axion [125], although a study of this is not yet available.…”
Section: Formation and Propertiesmentioning
confidence: 99%